2016
DOI: 10.1128/jvi.01381-16
|View full text |Cite
|
Sign up to set email alerts
|

The P Protein of Spring Viremia of Carp Virus Negatively Regulates the Fish Interferon Response by Inhibiting the Kinase Activity of TANK-Binding Kinase 1

Abstract: Spring viremia of carp virus (SVCV) is an efficient pathogen causing high mortality in the common carp. Fish interferon (IFN) is a powerful cytokine enabling host cells to establish an antiviral response; therefore, the strategies that SVCV uses to avoid the cellular IFN response were investigated. Here, we report that the SVCV P protein is phosphorylated by cellular TANK-binding kinase 1 (TBK1), which decreases IFN regulatory factor 3 (IRF3) phosphorylation and suppresses IFN production. First, overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In a water living environment, aquatic viruses can spread more easily and cause higher mortality than land-based viruses. In previous studies, our lab has reported that GCRV VP41 protein (encoded by the S8 segment) as well as SVCV N and P proteins antagonize fish RLR factors to reduce host IFN production [41][42][43], highlighting the evasion mechanisms used by aquatic viruses. To date, precise information regarding both the fish IFN response to viruses and the pathogenesis of aquatic viruses is rare;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a water living environment, aquatic viruses can spread more easily and cause higher mortality than land-based viruses. In previous studies, our lab has reported that GCRV VP41 protein (encoded by the S8 segment) as well as SVCV N and P proteins antagonize fish RLR factors to reduce host IFN production [41][42][43], highlighting the evasion mechanisms used by aquatic viruses. To date, precise information regarding both the fish IFN response to viruses and the pathogenesis of aquatic viruses is rare;…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of viral proteins has also been observed in aquatic viruses. For example, SVCV P protein can be phosphorylated by TBK1, which leads to the decline of IRF3 phosphorylation and IFN production [43]. However, the function of phosphorylated P protein in SVCV proliferation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to piscine MAVS and MITA , piscine TBK1 is also targeted by viruses as a major negative regulatory target to decrease the IFN response and facilitate viral replication. Spring viremia of carp virus (SVCV) P protein functions as a decoy substrate for cellular TBK1, leading to the reduction of IRF3 phosphorylation and suppression of IFN expression [ 155 ]. In zebrafish ( D. rerio ), a TBK1-like transcript (TBK1L), containing an incomplete S_TKc domain and lacking UBL_TBK1_like domain, was cloned.…”
Section: Alternative Splicing and Immune Function Of Downstream Simentioning
confidence: 99%
“…Several studies demonstrated that fish also possess a functional RLR pathway. For example, fish RIG-I and MDA5 have been shown to intensively trigger IFN production (22)(23)(24); IRF3 and MITA can be phosphorylated by TBK1, and they display a powerful capacity to activate IFN (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…6D, the phosphorylation of MITA caused by TBK1 was reduced dose dependently with the overexpression of VP41. In addition, our previous study demonstrated that IRF3 can also be phosphorylated by TBK1 (29). Next, it was worth investigating whether VP41 affects the TBK1-induced phosphorylation of IRF3.…”
mentioning
confidence: 99%